Cell proliferation, movement and differentiation during maintenance of the adult mouse adrenal cortex. - Su-Ping Chang; Hamish D Morrison; Frida Nilsson; Christopher J Kenyon; John D West; Steven D Morley (PLoS ONE)
Appropriate maintenance and regeneration of adult endocrine organs is important in both normal physiology and disease. We investigated cell proliferation, movement and differentiation in the adult mouse adrenal cortex, using different 5-bromo-2'-deoxyuridine (BrdU) labelling regimens and immunostaining for phenotypic steroidogenic cell markers. Pulse-labelling showed that cell division was largely confined to the outer cortex, with most cells moving inwards towards the medulla at around 13-20 µm per day, though a distinct labelled cell population remained in the outer 10% of the cortex. Pulse-chase-labelling coupled with phenotypic immunostaining showed that, unlike cells in the inner cortex, most BrdU-positive outer cortical cells did not express steroidogenic markers, while co-staining for BrdU and Ki67 revealed that some outer cortical BrdU-positive cells were induced to proliferate following acute adrenocorticotropic hormone (ACTH) treatment. Extended pulse-chase-labelling identified cells in the outer cortex which retained BrdU label for up to 18-23 weeks. Together, these observations are consistent with the location of both slow-cycling stem/progenitor and transiently amplifying cell populations in the outer cortex. Understanding the relationships between these distinct adrenocortical cell populations will be crucial to clarify mechanisms underpinning adrenocortical maintenance and long-term adaptation to pathophysiological states.